Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1038/clpt.1987.29
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fenoldopam, a dopaminergic agonist, on renal hemodynamics

Abstract: Fenoldopam, a dopaminergic agonist, was administered intravenously to 18 healthy male subjects in doses ranging from 0.025 to 1.0 microgram/kg/min for 2 hours. Three subjects were studied in a three-way crossover of fenoldopam at doses of 0.025, 0.10, and 0.50 microgram/kg/min. Fenoldopam decreased diastolic blood pressure and increased pulse rate without changing systolic blood pressure. Fenoldopam produced dose-related increases in para-aminohippuric acid clearance up to 75% at the 0.50 microgram/kg/min dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 2 publications
(2 reference statements)
2
30
0
5
Order By: Relevance
“…Possibly there is a difference in salt status of the subjects studied at the beginning of the studies, which might influence the results. In fact Schoors & Dupont (1990) observe a higher sodium excretion at baseline during the study day without lithium than was observed in our (Girbes et al, 1990) Allison et al (1987), who reported a dose-related decrease in diastolic blood pressure to a maximum of 6 mm Hg during fenoldopam infusion of 0.50 ,ug kgmin-. In hypertensive patients however, a marked decrease in blood pressure is found (Glueck et al, 1987;Murphy et al, 1987;Ventura et al, 1984 (1984).…”
mentioning
confidence: 41%
“…Possibly there is a difference in salt status of the subjects studied at the beginning of the studies, which might influence the results. In fact Schoors & Dupont (1990) observe a higher sodium excretion at baseline during the study day without lithium than was observed in our (Girbes et al, 1990) Allison et al (1987), who reported a dose-related decrease in diastolic blood pressure to a maximum of 6 mm Hg during fenoldopam infusion of 0.50 ,ug kgmin-. In hypertensive patients however, a marked decrease in blood pressure is found (Glueck et al, 1987;Murphy et al, 1987;Ventura et al, 1984 (1984).…”
mentioning
confidence: 41%
“…In low doses, it improves renal blood flow and glomerular filtration rate in both animals and healthy human volunteers. [10,11] Because of the receptor selectivity of fenoldopam, there is interest in its use as a renoprotective agent, although data regarding its effectiveness are contradictory. Small trials suggest fenoldopam can preserve renal function after ischemic injury during coronary artery bypass grafting or aortic aneurysm repair.…”
Section: Discussionmentioning
confidence: 99%
“…Like low-dose dopamine, it increases renal blood flow and glomerular filtration rate in both animals and healthy human volunteers. [10,11] Studies on the effectiveness of fenoldopam in preventing ARF in high-risk patients are conflicting. [12 -15] Furthermore, any salutary effects of fenoldopam on renal function may be dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the in vivo situation, the increase in PRA after fenoldopam could, at least in part, be related to the fall in blood pressure, resulting in a baroreflex-mediated increase in sympathetic tone, and hence Padrenoceptor-mediated renin release. Girbes et al (1990) did not provide any data on the blood pressure response to fenoldopam, but others have observed marked reductions in blood pressure in healthy volunteers, using similar doses (Allison et al, 1987). Using an infusion rate of fenoldopam of 0.05 ,ug kg-' min-1, a nondepressor dose which increases renal blood flow, Hughes et al (1988) could not demonstrate any change in PRA.…”
mentioning
confidence: 96%
“…Schoors refers to Allison et al (1987), who reported a dose-related decrease in diastolic blood pressure to a maximum of 6 mm Hg during fenoldopam infusion of 0.50 ,ug kgmin-. In hypertensive patients however, a marked decrease in blood pressure is found (Glueck et al, 1987;Murphy et al, 1987;Ventura et al, 1984).…”
mentioning
confidence: 99%